Autotaxin signaling facilitates β cell dedifferentiation and dysfunction induced by Sirtuin 3 deficiency - Cao, Huanyi (2023)
Objective: β cell dedifferentiation may underlie the reversible reduction in pancreatic β cell mass and function in type 2 diabetes (T2D). We previously reported that β cell-specific Sirt3 knockout (Sirt3f/f;Cre/+) mice developed impaired glucose tolerance and glucose-stimulated insulin secretion after feeding with high fat diet (HFD). RNA sequencing showed that Sirt3-deficient islets had enhanced expression of Enpp2 (Autotaxin, or ATX), a secreted lysophospholipase which produces lysophosphatidic acid (LPA). Here, we hypothesized that activation of the ATX/LPA pathway contributed to pancreatic β cell dedifferentiation in Sirt3-deficient β cells. Methods: We applied LPA, or lysophosphatidylcoline (LPC), the substrate of ATX for producing LPA, to MIN6 cell line and mouse islets with altered Sirt3 expression to investigate the effect of LPA on β cell dedifferentiation and its underlying mechanisms. To examine the pathological effects of ATX/LPA pathway, we injected the β cell selective adeno-associated virus (AAV-Atx-shRNA) or negative control AAV-scramble in Sirt3f/f and Sirt3f/f;Cre/+ mice followed by 6-week of HFD feeding. Results: In Sirt3f/f;Cre/+ mouse islets and Sirt3 knockdown MIN6 cells, ATX upregulation led to increased LPC with increased production of LPA. The latter not only induced reversible dedifferentiation in MIN6 cells and mouse islets, but also reduced glucose-stimulated insulin secretion from islets. In MIN6 cells, LPA induced phosphorylation of JNK/p38 MAPK which was accompanied by β cell dedifferentiation. The latter was suppressed by inhibitors of LPA receptor, JNK, and p38 MAPK. Importantly, inhibiting ATX in vivo improved insulin secretion and reduced β cell dedifferentiation in HFD-fed Sirt3f/f;Cre/+ mice. Conclusions: Sirt3 prevents β cell dedifferentiation by inhibiting ATX expression and upregulation of LPA. These findings support a long-range signaling effect of Sirt3 which modulates the ATX-LPA pathway to reverse β cell dysfunction associated with glucolipotoxicity.